Multiple change point analysis of hepatitis B reports in Xinjiang, China from 2006 to 2021 - Yang, Liping; Xie, Na; Yao, Yanru; Wang, Chunxia; RiFhat, Ramziya; Tian, Maozai; Wang, Kai (Frontiers in Public Health, 2023)
Objective: HB is a major global challenge, but there has been a lack of epidemiological studies on HB incidence in Xinjiang from a change point perspective. This study aims to bridge this gap by identifying significant change points and trends.The datasets were obtained from Xinjiang Information System for Disease Control and Prevention. Change points were identified using binary segmentation for the full datasets and segmented regression model for five age groups.The results showed four change points for quarterly HB time series, with the period between the first (March 2007) and second change point (March 2010) having the highest mean number of HB reports. In the subsequent segments, there was a clear downward trend in reported cases. The segmented regression model showed different numbers of change points for each age group, with the 30-50, 51-80 and 15-29 age groups having higher growth rates.2 This is a provisional file, not the final typeset article Conclusion: Change point analysis has valuable applications in epidemiology. These findings provide important information for future epidemiological studies and early warning systems for HB.